2020
DOI: 10.3389/fcimb.2019.00440
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Circulating Microbiome Signatures in Rheumatoid Arthritis

Abstract: Rheumatoid Arthritis (RA) has been increasingly associated with perturbations to the microbial communities that reside in and on the body (the microbiome), in both human and animal studies. To date, such studies have mainly focused on the microbial communities that inhabit the gut and oral cavity. Mounting evidence suggests that microbial DNA can be detected in the blood circulation using a range of molecular methods. This DNA may represent an untapped pool of biomarkers that have the potential to report on ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 69 publications
2
34
0
Order By: Relevance
“…Most bacteraemia and blood metagenomic studies employ methods such as PCI-extraction of blood fractions or systems such as the Phusion Blood Direct kit (Thermo Fisher Scientific), both of which generate total DNA (Amar et al, 2013;Rajendhran et al, 2013; Dinakaran et al, 2014;Lelouvier et al, 2016;Paisse et al, 2016;Gosiewski et al, 2017;Li et al, 2018;Castillo et al, 2019;Hammad et al, 2019). These studies tend to show Proteobacteria as the dominant phylum found in blood, but with high variability between studies at lower taxonomic levels, even taking into account diseaseassociated dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most bacteraemia and blood metagenomic studies employ methods such as PCI-extraction of blood fractions or systems such as the Phusion Blood Direct kit (Thermo Fisher Scientific), both of which generate total DNA (Amar et al, 2013;Rajendhran et al, 2013; Dinakaran et al, 2014;Lelouvier et al, 2016;Paisse et al, 2016;Gosiewski et al, 2017;Li et al, 2018;Castillo et al, 2019;Hammad et al, 2019). These studies tend to show Proteobacteria as the dominant phylum found in blood, but with high variability between studies at lower taxonomic levels, even taking into account diseaseassociated dysbiosis.…”
Section: Discussionmentioning
confidence: 99%
“…Streptococcal species of the viridans group, containing the Streptococcus mitis (S. mitis) group are the taxa most commonly associated with community-acquired native valve infective endocarditis. Periodontitis, oral pathogens and the dysbiotic oral microbiome have also been linked to the aetiology of other inflammatory diseases such as rheumatoid arthritis (Loyola-Rodriguez et al, 2010;Zhang et al, 2015;Konig et al, 2016;Beyer et al, 2018;Correa et al, 2019;Gomez-Banuelos et al, 2019;Hammad et al, 2019), late onset Alzheimer's disease (Singhrao and Olsen, 2019) and type II diabetes, which has been linked to distinct microbiomes in the gut (Wellen and Hotamisligil, 2005;Larsen et al, 2010), blood (Qiu et al, 2019), and oral cavity (Long et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, a manuscript from Hammad and co-authors described the profiles of circulating microbial DNA in patients with rheumatoid arthritis (RA) in comparison with patients affected by ankylosing spondylitis (AS) or psoriatic arthritis (PA) and healthy control subjects [ 46 ]. Bacterial community members were identified by sequencing of the 16S rRNA variable region 4 in all samples.…”
Section: Circulating 16s In a Disease Contextmentioning
confidence: 99%
“…See Supplementary Figure 3. Dinakaran et al, 2014;Lelouvier et al, 2016;Paisse et al, 2016;Gosiewski et al, 2017;Li et al, 2018;Castillo et al, 2019;Hammad et al, 2019). These studies tend to show Proteobacteria as the dominant phylum found in blood, but with high variability between studies at lower taxonomic levels, even taking into account diseaseassociated dysbiosis.…”
Section: Real-time Pcr Quantification Of Total and Streptococcal 16smentioning
confidence: 99%